Wstrętne przypadłości ciała w poezji Eugeniusza Tkaczyszyna-Dyckiego - Kijek, Dominika (Przestrzenie Teorii, 2013)
This article presents a confrontation of consciousness with bodiliness and physiology which can be observed in the poetry of Eugeniusz Tkaczyszyn-Dycki. Dycki points out that there is no such thing as a disembodied consciousness and makes the attempts to cross borders which are determined by language. He tries to get through to the semiotic sources of subjectivity, paying attention to the fact that a human is not able to get out of the cultural burden. The body and physiology, in this poetry, have the transgressive potential which invalidate binary oppositions. The sublimation of abject, putting emphasis on the processes of disgust/rejection as the foundation of self-image formation, allow Dycki to weaken the power of the symbolic system and episodically elude the paternalistic order.